The Impact of COVID-19 Epidemic on the Development of the Digital Economy of China—Based on the Data of 31 Provinces in China - Xu, Aidi; Qian, Fangbin; Pai, Chih-Hung; Yu, Na; Zhou, Pan (Frontiers in Public Health, 2022)
This study investigates the impact of the dissemination of information about the coronavirus disease 2019 (COVID-19) on China's level of economic develop-ment by measuring the HP financial index as an alternative variable of the digital economy. The empirical study shows that China's economy developed further with the dissemination of COVID-19 information. Furthermore, the digital economy increased the level of economic development more prominently at the onset of the pandemic. Moreover, an analysis of regional heterogeneity reveals that the eastern region maintained economic stability through its digital economy during COVID-19, while the central region improved its digital economy during this pandemic. Although the economically underdeveloped western region has not suffered too seriously from the pandemic, considering the disease’s sustained impact and the uncertainty of its transmission speed, the region should vigorously develop its digital economy to manage public risk.